Investigating the opportunity to increase yield by means of froth washing on mechanical coal flotation cells - Du Plessis, Cherryl (My University, 2018)
Froth washing is a process where water is injected or sprayed onto or into the froth to remove or flash-down gangue particles present in the froth because of hydraulic entrainment. This process was recently tested at Anglo American’s Goedehoop South (GHS) Flotation plant to evaluate its effects on the yield and product quality during coal fines flotation. The research aimed to design a suitable and effective froth wash system, and to use this design to test froth washing. The most suitable froth wash design was found to be a lip wash design. The performance of flotation cells with lip washing were compared to flotation without lip washing. The primary goal of the study was to determine whether lip washing on flotation cells can improve yield while maintaining the required product quality. The flotation plant produces an A grade thermal coal product with a target product calorific value (CV) of 27.30 MJ/kg (air dry basis), known within Anglo thermal coal as an AAC product. The test work compared different scenarios of lip wash against the current plant performance. This was done by sampling two identical flotation lines feeding from the same head box. One flotation line was run at the current optimum plant operating parameters to represent the current plant performance. On the other line a lip wash design was installed and different scenarios were applied to the lip wash line. The flotation reagent dosage on the flotation cells line without lip washing was kept constant at 1.3 kg/t which corresponds to the optimized plant operating dosage. The flotation reagent dosage on the flotation line with lip washing was varied between 1.3 kg/t and 1.75 kg/t to determine the optimum dosage rate that could be used when applying lip wash. Various configurations of froth washing was also tested, washing was either done on the primary flotation cell, i.e. primary wash only (PWO) or on the secondary flotation cell which is fed from the underflow of the primary cell, i.e. secondary wash only (SWO) or on both primary and secondary cells. Some experimental runs were done at specific settings to evaluate the effects of lip wash when different feed types are used. All the lip washing tests were compared with a baseline test where no lip washing was done (and therefore to current plant performance). The results of the test work showed that lip washing can increase product yields on the flotation cells by 8% - 40%, depending on the type and quality of the feed fed to the cells. Lip wash can increase yields without compromising product quality for reagent dosages of 1.3kg/ton-1.45kg/ton. An interesting observation was that lip wash increased yields while achieving similar product qualities at the current plant’s optimum reagent dosage of 1.3kg/ton, contrary to froth wash studies in literature where froth wash leads to a decrease in yield and increase in product quality. Primary wash only (PWO) was found to achieve higher product yield than secondary wash only (SWO), however the resultant product quality was found to be poorer than that achievable by SWO and baseline flotation cells. SWO produced higher yields than baseline cells while achieving a better product quality as well. The advantages of applying lip wash were found to be significantly higher when washing poorer feed material that results in low yields in the conventional flotation plant without lip wash (yields between 10%-40%). Yield increases between 30-40% were observed when lip wash is introduced to flotation cells floating low yielding coals. The mechanisms that are potentially responsible for the increased yield and high product qualities when lip washing is applied are a combination of the following: i. The increased froth mobility due to lip wash ii. Lip wash water washing hydraulically entrained material out of the froth phase and back to the pulp phase iii. The reduced residence time on the secondary cleaning stage resulting in a reduction in coalescence of bubbles in the froth phase.
MSc (50/50) School of Chemical and Metallurgical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, South Africa July, 2018
Keywords: Coal--Processing; Clean coal technologies